2019
DOI: 10.5194/esd-10-91-2019
|View full text |Cite
|
Sign up to set email alerts
|

ESD Reviews: Model dependence in multi-model climate ensembles: weighting, sub-selection and out-of-sample testing

Abstract: Abstract. The rationale for using multi-model ensembles in climate change projections and impacts research is often based on the expectation that different models constitute independent estimates; therefore, a range of models allows a better characterisation of the uncertainties in the representation of the climate system than a single model. However, it is known that research groups share literature, ideas for representations of processes, parameterisations, evaluation data sets and even sections of model cod… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
142
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 136 publications
(146 citation statements)
references
References 68 publications
1
142
0
3
Order By: Relevance
“…Twelve GCM outputs (shown in bold) ranking from the best performing to the worst are summarized in Table 2; the SU filter shows that the top four performing GCMs were ACCESS1.3, MIROC-ESM, MIROC-ESM-CHM, and NorESM1-M. These results further verified [16], who suggested that GCMs should meet these criteria. The top four GCMs were selected according to their higher SU weight and common performance.…”
Section: Selection Of Gcm Ensemblesupporting
confidence: 55%
“…Twelve GCM outputs (shown in bold) ranking from the best performing to the worst are summarized in Table 2; the SU filter shows that the top four performing GCMs were ACCESS1.3, MIROC-ESM, MIROC-ESM-CHM, and NorESM1-M. These results further verified [16], who suggested that GCMs should meet these criteria. The top four GCMs were selected according to their higher SU weight and common performance.…”
Section: Selection Of Gcm Ensemblesupporting
confidence: 55%
“…It has been argued that using a measure for model interdependence is important in so-called 'ensembles of opportunity' such as CMIP5, which are not designed to represent independent realizations of the climate system (e.g. Abramowitz et al 2019). An in-depth investigation of the independence weighting, e.g.…”
Section: Discussion Conclusion and Outlookmentioning
confidence: 99%
“…It therefore becomes important when incorporating SMILEs into a multi-model ensemble that uncertainty estimates reflect effective degrees of freedom in the ensemble (Pennell and Reichler, 2011). This can be achieved by down-weighting redundant information by a measure of independence (Abramowitz et al, 2019).…”
mentioning
confidence: 99%